BIOPOLITICAL FORM OF GOVERNANCE AND IDEOLOGICAL ISSUES IN MEDICINAL PATENTS: CRITICAL STUDY OF CORPORATE PREROGATIVE - Lilienthal, Gary Lilienthal (AR-RĀ’IQ, 2023)
A new biopolitical form of governance, in today’s late-stage capitalism, has essentially extinguished the inventor’s exclusive rights at the point of discovery, as the inventors or patent holders are a mere subjugated lifeworld. The general research objective of this article is to analyse critically the ideological issues in medicinal patents. The research question asked about meaning of the progress of medicinal science and its useful arts, arising from medicinal inventions and discoveries. The rhetoric of property in patent law has become a Darwinian struggle for survival of the most dominant corporate actors, through ownership of medicines to maintain life. Discussion seeks to sustain the view that progress of both medicinal science and its useful arts represents a wholly unreasoned mental concept that is really dominant through a corporate prerogative to own the molecules of medicines that maintain life, thereby extinguishing the inventor’s exclusive rights. Thus, the article critically analyses the legal narrative, through the lens of ideology in times of late-stage capitalism.